PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT EKSPERTA PRIATNA SINERGI TANGERANG SELATAN - Submission JORAPI; Sanyyah Putri Rahmadhani; Ida Nurlina (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine how the influence of motivation and leadership on employee performance at PT Eksperta Priatna Sinergi South Tangerang. The method used is quantitative method. The sampling technique used saturated sampling with a research sample of 66 respondents. The results of this study are, Motivation (X1) affects employee performance (Y) with the regression equation Y = 17.833 + 0.592 X1, the coefficient of determination is 0.433 or 43.3% and the correlation coefficient is 0.658. Hypothesis testing obtained a value (tcount 6.994> ttable 1.998), and a significance value (0.000 <0.05) then Ho1is rejected and Ha1 is accepted. This means that there is a significant effect of motivation (X1) on employee performance (Y) on the performance of employees of PT Eksperta Priatna Sinegi South Tangerang. Leadership (X2) affects employee performance (Y) with the regression equation Y = 21.881 + 0.496 X2, the coefficient of determination is 0.334 or 33.4% and the correlation coefficient is 0.578. Hypothesis testing obtained a value (tcount 5.666 > ttable value 1.998), and a significance value (0.000 <0.05) then Ho2 is rejected and Ha2 is accepted. This means that there is a significant influence of leadership (X2) on employee performance (Y) on the performance of employees of PT Eksperta Priatna Sinegi South Tangerang. Motivation (X1) and Leadership (X2) affect employee performance (Y) with the regression equation Y = 17.493 + 0.531 X1 + 0.069 X2, the coefficient of determination is 0.435 or 43.5% and the correlation coefficient is 0.660. Hypothesis testing Fcount value 24.264 > Ftable 3.14. This proves that Ho3 is rejected and Ha3 is accepted. This means that there is a significant effect of motivation and leadership on employee performance at PT Eksperta Priatna Sinegi South Tangerang.